Art after conceptual art - Alberro, Alexander; Buchmann, Sabeth (Cambridge, Mass. : MIT Press ; Vienna, Austria : Generali Foundation, 2006)
The way out is the way in / Alexander Alberro ## Allegorical procedures : appropriation and montage in contemporary art / Benjamin H.D. Buchloh ## Unwritten histories of conceptual art / Thomas Crow ## House work and art work / Helen Molesworth ## Within the organic line and after / Ricardo Basbaum ## Language, reality, irony : the art books of Jarosław Kozłowski / Luiza Nader ## Conceptual expression : on conceptual gestures in allegedly expressive painting, traces of expression in proto-conceptual works, and the significance of artistic procedures / Isabelle Graw ## Heterotopias of the cinematographic : institutional critique and cinema in the art of Michael Asher and Dan Graham / Gregor Stemmrich ## Letting loos(e) : institutional critique and design / Helmut Draxler ## Transgressing boundaries (even those marked out by the predecessors) in new genre conceptual art / Edit András ## Under the sign of labor / Sabeth Buchmann ## The lack of interest in Maria Eichhorn's work / Elizabeth Ferrell ## Pre post : speaking backwards / Henrik Olesen.
Includes bibliographical references and index.
boek